Proposal for an instrument for teacher evaluation at UNAN-MANAGUA. (Revista Electrónica Calidad en la Educación Superior, 2021)
This article describes the procedures applied to the proposal of an evaluation instrument at the National University of Nicaragua, in response to the recently approved curricular changes; and presents the results of the Confirmatory Factor Analysis as applied to the questionnaire, using a scale of four adjectives of ordinal metering. There is a sample of 773 students to analyse the reliability and structural validity through a CFA. Results show that the three-factor model proposed presents high quality indexes of adjustment. The CFA of this model confirms that this questionnaire meets the technical requirements to be applied as an evaluation instrument.
Keywords: Assessment, factor analysis, questionnaire.